2022
DOI: 10.1109/tte.2022.3158838
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Performance and Cycle Life Improvements in the Latest Generations of Prismatic Lithium-Ion Batteries

Abstract: During the last decade, the market interest for electrified vehicles has increased considerably alongside global climate initiatives. This has coincided with vast improvements in automotive-grade, lithium-ion battery performance. This has increased the range of battery electric vehicles and plug-in hybrids but lifetime remains a challenge. Ageing during fast charging is especially difficult to understand due to its non-linear dependence on charge rate, state-of-charge and temperature. We present results from f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…The cells were subjected to both calendar and cycle ageing, varying SoC and temperature in the former case and C-rate, DoD and temperature in the latter case; it is found that the temperature is the main parameter that affects the capacity fade and resistance increases for both calendar and cycle ageing [16]. However, identifying the ageing of an electrochemical cell is particularly difficult to understand due to its non-linear dependence on charge rate, state-of-charge and temperature [17]. In this regard, an interesting representation of the link between causes and effects in terms of ageing (evaluated with two main macro effects: capacity fade and power fade) has been presented [13].…”
Section: Introductionmentioning
confidence: 99%
“…The cells were subjected to both calendar and cycle ageing, varying SoC and temperature in the former case and C-rate, DoD and temperature in the latter case; it is found that the temperature is the main parameter that affects the capacity fade and resistance increases for both calendar and cycle ageing [16]. However, identifying the ageing of an electrochemical cell is particularly difficult to understand due to its non-linear dependence on charge rate, state-of-charge and temperature [17]. In this regard, an interesting representation of the link between causes and effects in terms of ageing (evaluated with two main macro effects: capacity fade and power fade) has been presented [13].…”
Section: Introductionmentioning
confidence: 99%